The Lasting Effects of a “Relentless Crisis”: The Great Recession and Health Inequalities in Spain - Juan Antonio Córdoba-Doña; Antonio Escolar-Pujolar (e-cadernos ces)
Spain is generally regarded as one of the European countries most affected by the Great Recession starting in 2008 and subsequent restrictive policies. In the first part of this paper we attempt to understand the impacts of the crisis on the welfare state that have led to health inequalities, with a special emphasis on the history of the Spanish National Health System from mid-twentieth century onwards. We also examine citizens’ responses to austerity measures within the health system, highlighting the role of the “white tides” movement. In the second part of the paper, we provide a selective review of the main findings on the effects of the Great Recession in the country, focusing particularly on its outcomes on mental health and on inequalities in health and healthcare use. We conclude that key policies need to be directed towards “the causes of the causes” of health inequalities, a complicated challenge in the current phase of capitalism.